Shape memory effect in 3D-printed scaffolds for self-fitting implants. (August 2017) - Senatov, F.S.; Zadorozhnyy, M.Yu.; Niaza, K.V.; Medvedev, V.V.; Kaloshkin, S.D.; Anisimova, N.Yu; Kiselevskiy, M.V.; Yang, Kai-Chiang
Graphical abstract: Highlights: Introduction of HA nanoparticles results in higher SME activation energy. Shape programming at 64 °C led to the maximum recovery stress. Accumulation of defects led to decrease in shape recovery rate and recovery stresses. 3D-printed PLA/HA scaffolds support MSCs survival and stimulate active proliferation. Abstract: 3D-printed porous scaffolds based on polylactide (PLA)/15% wt. nano-hydroxyapatite (HA) with shape memory effect (SME) for self-fitting implants were studied. Introduction of HA nanoparticles into the PLA matrix had an effect on the ordering of polymer molecular chains. The presence of HA nanoparticles caused a change in friction between molecular chains during the glass transition. Apparent activation energies of SME for PLA and PLA/HA 3D-printed samples were 490 and 555 kJ/mol, respectively. HA nanoparticles acted as centers for the formation of additional rigid fixed phase that governed shape memory properties. The maximum recovery stress was observed in case of shape programming in the glass transition interval at 64 °C. However, cyclic SME tests showed that the increase in number of cycles "programming – SME activation" led to decrease in shape recovery rate and recovery stresses due to accumulation of defects. It was demonstrated that 3D-printed porous PLA/HA scaffolds support mesenchymal stromal cells (MSCs) survival, and stimulate active proliferation of the cells as well. Such scaffolds with SME colonized by MSCs have the potential to be used as self-fitting implants for bone replacement and could also be beneficial in the engineering of complex tissues. MSCs colonization of scaffold favors vascularization of the implant, which is essential for the successful bone prosthesis.